Crime, harm and consumerism - Hall, Steve, 1955-; Kuldova, Tereza; Horsley, Mark (Milton : Routledge, 2020)
This book offers a collection of cutting-edge essays on the relationship between crime, harm and consumer culture. Although consumer culture has been addressed across the social sciences, it has yet to be fully explored in criminology. The editors bring together an impressive list of authors with original ideas and a fresh perspective to this field. The collection first introduces the reader to three sets of ideas which will be especially useful to students and researchers piecing together theoretical frameworks for their studies. New concepts such as pseudo-pacification, the materialist libertine and the commodification of abstinence can be used as foundation stones for new explanatory criminological analyses in the 21st century. The collection then moves on to present case studies based on rigorous empirical work in the fields of consumption and debt, outlaw' gangs, illegal drug markets, gambling, the mentality that drives investment fraudsters and the relationship between social media and state surveillance. These case studies showcase the strength of the research skills and knowledge these scholars offer to the field of criminology. Written in a clear and direct style, this book will appeal to students and scholars in criminology, sociology, cultural studies, social theory and those interested in learning about the effects of consumer culture in modern society.
"This book offers a collection of cutting-edge essays on the relationship between crime, harm and consumer culture. Although consumer culture has been addressed across the social sciences, it has yet to be fully explored in criminology. The editors bring together an impressive list of authors with original ideas and a fresh perspective to this field. The collection first introduces the reader to three sets of ideas which will be especially useful to students and researchers piecing together theoretical frameworks for their studies. New concepts such as pseudo-pacification, the materialist libertine and the commodification of abstinence can be used as foundation stones for new explanatory criminological analyses in the 21st century. The collection then moves on to present case studies based on rigorous empirical work in the fields of consumption and debt, 'outlaw' gangs, illegal drug markets, gambling, the mentality that drives investment fraudsters and the relationship between social media and state surveillance. These case studies showcase the strength of the research skills and knowledge these scholars offer to the field of criminology. Written in a clear and direct style, this book will appeal to students and scholars in criminology, sociology, cultural studies, social theory and those interested in learning about the effects of consumer culture in modern society"--
7 Gambling and harm in 24/7 capitalism: reflections from the post-disciplinary present -- 8 Toxic sovereignty: understanding fraud as the expression of special liberty within late capitalism -- 9 Spy vs Spy: the surveillance state of social media -- Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Criminology; Consumption (Economics) -- Case studies; Criminology -- Case studies